2016
DOI: 10.4314/rj.v3i1.4f
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and attitudes of nurses regarding pain in the intensive care unit patients in Rwanda

Abstract: Background: Pain is a significant burden experienced by patients admitted to the adult Intensive Care Unit (ICU). Acute

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(40 citation statements)
references
References 14 publications
5
35
0
Order By: Relevance
“…e majority of nurses in the study did not have any formal training on paediatric pain management. is is in line with a study in Rwanda by Ufashingabire et al[11] and Zeb et al[18] in Pakistan where most of the nurses 59.4% and 83.3%, respectively, had no formal training on paediatric pain management.…”
supporting
confidence: 91%
See 1 more Smart Citation
“…e majority of nurses in the study did not have any formal training on paediatric pain management. is is in line with a study in Rwanda by Ufashingabire et al[11] and Zeb et al[18] in Pakistan where most of the nurses 59.4% and 83.3%, respectively, had no formal training on paediatric pain management.…”
supporting
confidence: 91%
“…Nurses per their training are often expected to have a good knowledge of pain management. However, studies showed that some nurses working with children have poor knowledge and practices with regard to paediatric pain management [2,11,12]. Studies by Aziato and Adejumo [13] revealed that nurses' inadequate pain management knowledge might have resulted from numerous causes such as curriculum gaps during training, inadequate clinical supervision, and lack of funding for organizing regular workshops.…”
Section: Introductionmentioning
confidence: 99%
“…al who found that oncology nurses lacked sufficient knowledge regarding pain management among cancer pain ) 11 (. The study was also supported by study done in Rwanda by Ufashingabire et al, who found that nurses working in ICU had poor knowledge and bad attitudes towards pain assessment and management (12). This finding was in good agreement with that obtained by Tufekci et al have identified knowledge deficits about pain management and health care professionals misconceptions about pain as the major challenge towards effective pain management.…”
Section: Discussionsupporting
confidence: 84%
“…One Rwandan study showed that nurses in an adult intensive care unit lacked adequate knowledge and had a poor attitude towards pain management. [14] This paper introduces the background and significance of neonatal pain management. The short-and long-term complications of failing to recognise and relieve neonatal pain are presented.…”
Section: Introductionmentioning
confidence: 99%